Pengaruh Model Discovery Learning terhadap Keterampilan Menulis Teks Eksposisi Siswa Kelas X SMA Negeri 2 Kota Sungai Penuh - Agustin, Reva; R, Syahrul (MASALIQ, 2023)
The purpose of this study was to describe the effect of using the discovery learning model on the writing skills of exposition texts of class X students of SMA Negeri 2 Sungai penuh city. This type of research is a quantitative research with the one group pretest-posttest design experimental method. The population of this study were class X students of SMA Negeri 2 Sungai penuh City who were enrolled in the 2022/2023 academic year with a total of 212 students. The sample of this research was students of class X IPA 4, totaling 34 people who were determined using a purposive sampling technique. The data in this study were the scores of the exposition text writing skills test scores of class X students of SMA Negeri 2 Kota Sungai Penuh before and after using the discovery learning model. The research instrument was a performance test, namely a test of writing skills of expository text. Furthermore, the data were analyzed using the percentage formula, the arithmetic mean formula, and the t-test. Based on the results of the study concluded the following three things. First, the skills of writing explanatory texts for class X students of SMA Negeri 2 Kota Sungai Penuh before using the discovery learning model are in the Enough qualification (C) with an average value of 59.57. Second, the writing skills of exposition texts for class X students of SMA Negeri 2 Kota Sungai Penuh after using the discovery learning model are in the Good qualification (B) with an average score of 79.40. Third, based on the t-test, the alternative hypothesis (H1) is accepted at the level of confidence and degrees of freedom (dk) = (n-1) because tcount>ttable (8.89>1.80). In other words, the discovery learning model has an effect on the exposition text writing skills of class X students of SMA Negeri 2 Sungai penuh City.